2009
DOI: 10.1002/ctpp.200910007
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Properties of Cylindrical Microhollow Cathode Discharges in Helium Using a Two‐Dimensional, Self‐Consistent Fluid Model

Abstract: In this paper, a numerical simulation model was developed to simulate the helium plasma in a cylindrical Microhollow cathode based on a two-dimensional, time-dependent and self-consistent fluid model. The aim of our work is to provide estimates of the main discharge and plasma parameters and to help understand the basic mechanisms governing the MHCD devices. Accurate solutions of the continuity equations, electron energy balance equation and possion's equation with realistic boundary conditions are obtained. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For example, Boeuf and Pitchford 7 used a fluid model to calculated current-voltage ͑I-V͒ characteristics of a sandwich type of MHCD. Gu et al 8 used a two-dimensional ͑2D͒ selfconsistent fluid model to predict the discharge properties of cylindrical MHCD. In the past, most researches focused on the cylindrical structure, while few works have been done on the rectangular MHCD, although it has also wide potential applications in laser, coating, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Boeuf and Pitchford 7 used a fluid model to calculated current-voltage ͑I-V͒ characteristics of a sandwich type of MHCD. Gu et al 8 used a two-dimensional ͑2D͒ selfconsistent fluid model to predict the discharge properties of cylindrical MHCD. In the past, most researches focused on the cylindrical structure, while few works have been done on the rectangular MHCD, although it has also wide potential applications in laser, coating, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerical modelings are widely used to study these discharges. Several research works have employed fluid models to simulate MHCDs and discover their basic principles [27][28][29]. They found that MHCDs consist of two main regions: cathode fall (CF) and negative glow (NG).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small distance between the anode and cathode in MHCDs, no significant positive column is formed. Then, the ions generated in the NG are accelerated by the electric field and their density increases toward the cathode, reaches its maximum in the cathode sheath, and then collide with the cathode surface and emit secondary electrons [28]. These electrons are accelerated in the sheath strong field and then spend their energies by exciting the ground-state atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereinto, fluid models are founded on the numerical solution of Poisson equation, and they may cause computing errors originating from the non-equilibrium characters and nonlocal effects. And compared with the computationally demanding and time-consuming PIC/MCC (a hybrid of particle-in-cell and Monte Carlo collision) models, Monte Carlo technique is an accurate and straightforward statistical method to simulate the acting force and transient motion of electrons and ions in the cathode sheath and negative glow region [5,6].…”
Section: Introductionmentioning
confidence: 99%